Experimental Study on Well Placement Optimization for Steam-Assisted Gravity Drainage to Enhance Recovery of Thin Layer Oil Sand Reservoirs - Lei Tao; Xiao Yuan; Hao Cheng; Bingchao Li; Sen Huang; Na Zhang (Geofluids)
SAGD (steam-assisted gravity drainage) technique is one of the most efficient thermal recovery technologies for exploiting Mackay River thin layer oil sand reservoirs. However, when making use of the traditional SAGD technique (the production and injection well are located on the same axis with the horizontal well spacing of 0 m), the steam chamber development is usually insufficient because of the high longitudinal sweep rate of steam, which seriously influences the SAGD performance for developing thin layer oil sand reservoirs especially. It is extremely important to find an economical and practicable method to promote the steam chamber development in thin oil sand reservoirs in the process of SAGD production; optimizing well placement is a reliable method. In this paper, an improved well placement method is proposed to enhance production performance of traditional SAGD, which is changing the horizontal well spacing to place the production well below of the side of the injection well (two wells are not located on the same axis). Three groups of 2D visualization experiments with different horizontal distances between two wells (0 cm, 10 cm, and 20 cm) were carried out, respectively, to observe the development and change of the steam chamber development, and to explore the EOR mechanisms. On the 2D experiment basis, optimal horizontal distance was selected to perform 3D physical simulation experiment to study and verity the production mechanism systematically. The results of 2D visualization experiment showed that the final oil recoveries of experimental groups with 10 cm and 20 cm horizontal distances were 7.6% and 2.3% higher than those of traditional SGAD (horizontal distance was 0 cm), respectively. Combined with 3D experimental results, the change in the horizontal relative position of two wells makes the steam first spread laterally between injecting and producing wells; thus, the lateral development of the steam chamber was promoted, and changes of temperature field also display that the lateral sweep area of steam was increased obviously and the form of steam chamber is changed. Meanwhile, the generation of appropriate horizontal well spacing can combine the effect of steam displacement and gravity drainage better and improve the sweep efficiency of steam. Nevertheless, the overlarge horizontal well spacing will also hinder the steam chamber development because the strength of steam overlap is weakened. Furthermore, the findings of this study help for better understanding that changing the horizontal well spacing can promote the lateral development of steam chamber, which can be used to enhance the oil recovery of thin layer oil sand reservoirs especially.